Repeated-sprint sequences during female soccer matches using fixed and individual speed thresholds - Nakamura, F. Y.; Pereira, L. A.; Loturco, I.; Rosseti, M.; Moura, F. A.; Bradley, P. S. (The Journal of Strength and Conditioning Research, 2017)
The main objective of this study was to characterize the occurrence of single sprint and repeated-sprint sequences (RSS) during elite female soccer matches, using fixed (20 km·h-1) and individually based speed thresholds (>90% of the mean speed from a 20-m sprint test). Eleven elite female soccer players from the same team participated in the study. All players performed a 20-m linear sprint test, and were assessed in up to 10 official matches using Global Positioning System technology. Magnitude-based inferences were used to test for meaningful differences. Results revealed that irrespective of adopting fixed or individual speed thresholds, female players produced only a few RSS during matches (2.3 ± 2.4 sequences using the fixed threshold and 3.3 ± 3.0 sequences using the individually based threshold), with most sequences composing of just 2 sprints. Additionally, central defenders performed fewer sprints (10.2 ± 4.1) than other positions (fullbacks: 28.1 ± 5.5; midfielders: 21.9 ± 10.5; forwards: 31.9 ± 11.1; with the differences being likely to almost certainly associated with effect sizes ranging from 1.65 to 2.72), and sprinting ability declined in the second half. The data do not support the notion that RSS occurs frequently during soccer matches in female players, irrespective of using fixed or individual speed thresholds to define sprint occurrence. However, repeated-sprint ability development cannot be ruled out from soccer training programs because of its association with match-related performance.